Memotret panggung depan dan panggung belakang pengguna media sosial studi kasus pada panggung twitter di Indonesia - Rija Faiza (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
This study discusses the communication behavior of Twitter social media users in Indonesia because there are public concerns about the rise of hate speech on Twitter social media. The purpose of this study was to analyze the front stage and back stage of Twitter social media users in Indonesia using Dramaturgy theory. The method used is using qualitative methods with data collection techniques through secondary data. The result of this study is that Twitter social media users in Indonesia use the front stage when using social media because it is indicated to play a different role on an account, while the back stage of Twitter social media is a relaxation area or as their diary.